A comparison of measured and modelled energetics, estimated from global positioning systems (GPS) velocity - ROBERT OWEN (2022)
Introduction:Traditionally in laboratory settings, indirect calorimetry and blood lactate B[La] analysis provide a criterion measure of bioenergetics, although it is not feasible within a multitude of competitive sports. Mathematical modelling provides a solution to estimate metabolic power during competitive sport, whereby a sprint running model was proposed, using global positioning systems (GPS) velocity data and the known energy cost of the equivalent slope running. Now a novel mechanical approach has been presented as an alternative model to estimate metabolic power from GPS velocity data and principles of the work-energy theorem. The purpose of this study was to compare metabolic power as produced from the sprint running model, the mechanical model and indirect calorimetry. Methods:Thirteen participants performed a maximal effort 400 m- and a repeated 40 m- sprint and sub-maximal continuous running and repeated 20 m shuttle running test. The tests were completed across two testing sessions a week apart. In all tests, through exercise and recovery periods, V̇ O2 was measured by single breath analysis and B[La] was sampled during the recovery. The sum of V̇ O2 and B[La] determined the energy cost. GPS velocity data collected throughout each test was processed through the sprint running and mechanical models to estimate energy cost. Results:Indirect calorimetry determined significantly greater values of overall metabolic power than sprint running (P < 0.001) and mechanical (P < 0.001) models across all exercise tests, and the mechanical model estimated larger overall metabolic power values than the sprint running model. Conclusion:This study urges sports scientists to understand the constructs of modelling bioenergetics and the inherent limitations of modelled energetics before implementing them within professional practice. Modelled bioenergetics may provide an estimation of the aerobic energy demand of overground running during exercise but is unable to account for the increased metabolic supply post-exercise.